Comparison of the nephrotoxic effects of iodixanol versus iopamidol in patients with acute coronary syndrome - Gul, Mehmet; Turan, Burak; Ugur, Murat; Turer, Ayca; Findikcioglu, Ugur; Ergelen, Mehmet; Uyarel, Huseyin (My University, 2013)
Objectives: The iso-osmolar contrast agent iodixanol may be associated with fewer contrast-induced acute kidney injuries when compared with low-osmolar contrast agents. The aim of this study was to compare iodixanol and iopamidol in patients with acute coronary syndrome (ACS) who were undergoing coronary angiography.